Celebrity Worship And Impulsive Buying Among Early Adults : Evidence From Korean Wave Fans - Nibraas Faadiyah Suhana; Eka Dian Aprilia; Risana Rachmatan; Arum Sulistyani (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
The Korean Wave as a global popular culture phenomenon has significantly shaped consumer behavior, including the tendency of celebrity worship that may lead to impulsive buying. While developmental theory suggests that idol worship decreases in early adulthood, studies in Indonesia indicate that this behavior remains prevalent among Korean Wave fans. This study uses a quantitative research design with a correlation method. The sampling technique used non-probability sampling method with accidental sampling technique with a total sample size of 193 early adults (18-25 years old) Korean Wave fans. Data collection was carried out using the Impulsive Buying Tandency Scale (IBTS) and Celebrity Attitude Scale (CAS). The hypothesis of this study was tested using Pearson Product-Moment Correlation, showing the results that there is a relationship between the dimensions of celebrity worship (entertainment social, intense personal, and borderline pathological) with impulsive buying with a significance value (p) = 0.000. The higher the celebrity worship dimensions (entertainment social, intense personal, and borderline pathological) in early adult Korean Wave fans, the higher the impulsive buying they have. Conversely, the lower the celebrity worship dimensions (entertainment social, intense personal, and borderline pathological) in early adult Korean Wave fans, the lower the impulsive buying they have.Abstrak: Fenomena Korean Wave sebagai budaya populer global telah memengaruhi perilaku konsumsi masyarakat, termasuk kecenderungan celebrity worship yang berhubungan dengan pembelian impulsif. Meskipun teori perkembangan menjelaskan bahwa intensitas pemujaan idola menurun pada masa dewasa awal, penelitian di Indonesia menunjukkan masih tingginya perilaku tersebut pada penggemar Korean Wave. Penelitian ini menggunakan desain penelitian kuantitatif dengan metode korelasi. Teknik pengambilan sampel menggunakan metode non-probability sampling dengan teknik accidental sampling dengan jumlah sampel sebanyak 193 dewasa awal (18-25 tahun) penggemar Korean Wave. Pengumpulan data dilakukan menggunakan skala Impulsive Buying Tandency Scale (IBTS) dan Celebrity Attitude Scale (CAS). Hipotesis penelitian ini diuji menggunakan Pearson Product-Moment Correlation, dengan menunjukkan hasil terdapat hubungan antara dimensi celebrity worship (entertainment social, intense personal, dan borderline pathological) dengan impulsive buying dengan nilai signifikansi (p) = 0,000. Semakin tinggi dimensi celebrity worship (entertainment social, intense personal, dan borderline pathological) pada dewasa awal penggemar Korean Wave, semakin tinggi pula impulsive buying yang mereka miliki. Sebaliknya, semakin rendah dimensi celebrity worship (entertainment social, intense personal, dan borderline pathological) pada dewasa awal penggemar Korean Wave, semakin rendah pula impulsive buying yang dimiliki.